PENGARUH LAMA PENYIMPANAN INFUSED WATER LEMON (Citrus limon) dan MENTIMUN (Cucumissativus L) TERHADAP PERTUMBUHAN BAKTERI - M. I. Chandra; Susie Amilah (FMIPA : Universitas PGRI Adi Buana, 2017)
This study aims to determine the effect of long storage of infused water lemon (Citrus limon) and cucumber (Cucumissativus L) on bacterial growth. Infused water will be stored for 0 hours, 12 hours, 24 hours, 36 hours, and 48 hours at room temperature. This research uses experimental method. The sample used in this research is infused water lemon and infused water cucumber. The research was conducted in Bacteriology laboratory of Surabaya Health Analyst Department in January 2017 - March 2017. Data analysis was done by observing bacterial colony using total plate number by comparing the two sample treatments. Then proceed with statistical test Independent sample t-test about colony calculation results on infused water lemon and infused water cucumber. The final results show that there is an increase in the number of bacteria in the infused water lemon and infused water cucumber every hour. This increase in the number of bacteria can occur due to improper infusion of water storage, and several factors affecting infused water damage. Keywords : Infused water lemon, infused water cucumber, storage duration, bacterial growth, Total Plate Number.